The association of depressed angiogenic factors with reduced capillary density in the Rhesus monkey model of myocardial ischemia. Issue 7 (8th February 2016) - Zhang, Wenjing; Zhao, Xinmei; Xiao, Ying; Chen, Jianmin; Han, Pengfei; Zhang, Jingyao; Fu, Haiying; James Kang, Y.
Abstract : Copper loss in ischemic myocardium makes a critical contribution to the suppression of HIF-1-regulated angiogenesis. Abstract : Depressed capillary density is associated with myocardial ischemic infarction, in which hypoxia-inducible factor 1α (HIF-1α) is increased. The present study was undertaken to examine changes in the angiogenic factors whose expression is regulated by HIF-1 and their relation to the depressed capillary density in the Rhesus monkey model of myocardial ischemic infarction. Male Rhesus monkeys 2–3 years old were subjected to myocardial ischemia by permanent ligation of left anterior descending (LAD) artery leading to the development of myocardial infarction. Eight weeks after LAD ligation, copper concentrations, myocardial histological changes and capillary density were examined, along with Western blot and immunohistochemical analysis of angiogenic factors and detection of HIF-1 activity. Capillary density was significantly decreased but the concentrations of HIF-1α and HIF-1β were significantly increased in the infarct area. However, the levels of mRNA and protein for VEGF and VEGFR1 were significantly decreased. Other HIF-1 regulated angiogenic factors, including Tie-2, Ang-1 and FGF-1, were also significantly depressed, but vascular destabilizing factor Ang-2 was significantly increased. Copper concentrations were depressed in the infarct area. Copper-independent HIF-1 activity was increased shown by the elevated mRNA level of IGF-2, a HIF-1 target gene. Removal of copper by a copper chelator, tetraethylenepentamine, from primary cultures of neonatal rat cardiomyocytes also suppressed the expression of HIF-1 regulated VEGF and BNIP3, but not IGF-2. The data suggest that under ischemic conditions, copper loss suppressed the expression of critical angiogenic genes regulated by HIF-1, but did not affect copper-independent HIF-1 activation of gene expression. This copper-dependent dysregulation of angiogenic gene expression would contribute to the pathogenesis of myocardial ischemic infarction.